Mapping Interactive Voice Response Call Data in Developing Regions - Vashistha, Aditya; Cutrell, Ed; Thies, Bill (ACM CHI 2013 Workshop on Geographic Human-Computer Interaction, 2013)
In this position paper, we discuss the importance of adding location data to the information collected using Interactive Voice Response (IVR) systems in the developing world. We also discuss various approaches to input location data using basic phones, as well as open research questions.